1992
DOI: 10.18806/tesl.v9i2.602
|View full text |Cite
|
Sign up to set email alerts
|

Who Are Our Students? A Synthesis of Foreign and Second Language Research on Individual Differences with Implications for Instructional Practice

Abstract: Teachers of second or foreign languages, to be most effective, must understand who their students really are. This means teachers must comprehend differences among their students in many individual characteristics, such as age, sex, motivation, anxiety, self-esteem, tolerance of ambiguity, risk-taking, cooperation, competition, and language learning strategies and styles. This article synthesizes previous and current research on these individual differences among students and provides implications for instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 30 publications
1
47
0
3
Order By: Relevance
“…In addition, the level of teaching materials, learners' motivation levels, teachers, learners' perceptions of the target culture are some of the factors that are related to FLA (Bailey, 1983;Oxford, 1992;Price, 1991;Sparks & Ganschow, 1991;Young, 1990). However, the effects of FLA vary when the learning process and beneficial and harmful outcomes are considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the level of teaching materials, learners' motivation levels, teachers, learners' perceptions of the target culture are some of the factors that are related to FLA (Bailey, 1983;Oxford, 1992;Price, 1991;Sparks & Ganschow, 1991;Young, 1990). However, the effects of FLA vary when the learning process and beneficial and harmful outcomes are considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Learners' individual differences, such as age and learning strategies uses, have been ignored as a part of the instructional process. Many studies revealed that individual differences play an important role in second or foreign language acquisition (Ehrman, 1990;Galbraith & Gardner, 1988;Oxford, 1992;Oxford & Ehrman, 1993;Scarcella & Oxford, 1992;Skehan, 1989). Among these individual-difference variables, "language learning strategies appear to be among the most important variables influencing performance in a second language" (Oxford, 1989, p. 21).…”
Section: Introductionmentioning
confidence: 99%
“…While some of them indicated learners' beliefs about learning a foreign language, teachers' beliefs about teaching a foreign language, classroom procedures and testing as the main sources of anxiety (Young, 1990), the others showed the level of language course, language skills, motivation, and proficiency as being other factors arousing anxiety (Ellis & Rathbone, 1987;Oxford, 1992;Price, 1991;Sparks & Ganschow, 1991). But, it can be said prior studies focused on the identification of foreign language anxiety.…”
Section: Anxiety and Foreign Language Learningmentioning
confidence: 99%